DEVELOPING AN E-FLIPBOOK ON ENVIRONMENTAL CHANGE TOPICS TO DEVELOP STUDENTS’ DIGITAL LITERACY - Dinda Ainur Rachim; Reni Ambarwati (EDUSAINS, 2021)
PENGEMBANGAN E-FLIPBOOK MATERI PERUBAHAN LINGKUNGAN UNTUK MELATIHKAN LITERASI DIGITALAbstractDigital literacy is one of the abilities that students need to master in the 21st century. Therefore, this study aims to produce an e-flipbook of environmental change topics to train digital literacy, which is valid, practical, and effective. As a developmental study, it refers to a 4-D model, without a dissemination phase. The material validity was measured based on the validation by material, educational, and information-technology experts. Furthermore, the e-flipbook practicality was measured based on the practitioners and student responses. Also, the effectiveness was measured according to students' digital literacy based on normalized gain score, and the data were descriptive-quantitatively analyzed. The results showed the developed e-flipbook was declared valid based on the eligibility criteria for design, content, and language. Furthermore, it was stated to be practical according to the responses of practitioners and students with the acquisition of very practical and good categories. The e-flipbook was also declared effective with the acquisition of an average score of increasing digital student literacy by 0.7 in the high category. Therefore, it can be concluded that the e-flipbook on environmental change topic is valid, practical, and effective in learning digital literacy. AbstrakLiterasi digital merupakan salah satu kemampuan yang harus dikuasai peserta didik di abad ke-21. Tujuan penelitian ini adalah menghasilkan e-flipbook materi perubahan lingkungan untuk melatihkan literasi digital kelas X SMA yang layak digunakan, yaitu e-flipbook yang valid, praktis, dan efektif. Penelitian ini merupakan jenis penelitian pengembangan yang mengadaptasi model 4-D namun tahap penyebaran tidak dilakukan. Validitas e-flipbook diukur berdasarkan validasi ahli materi, ahli pendidikan, dan ahli IT. Kepraktisan e-flipbook ditinjau berdasarkan respons praktisi dan respons siswa. Keefektifan e-flipbook diukur berdasarkan tes literasi digital peserta didik berdasarkan gain score ternormalisasi. Data dianalisis secara deskriptif kuantitatif. Hasil penelitian menunjukan bahwa e-flipbook yang dikembangkan dinyatakan sangat valid berdasarkan kriteria kelayakan penyajian, isi, dan kebahasaan. E-flipbook yang dikembangkan dinyatakan praktis berdasarkan respons praktisi (guru) dan siswa dengan perolehan kategori sangat praktis dan sangat baik. E-flipbook yang dikembangkan dinyatakan efektif dengan perolehan skor rata-rata peningkatan literasi digital siswa sebesar 0.7 dengan kategori tinggi. Secara keseluruhan e-flipbook materi perubahan lingkungan dinyatakan valid, praktis, dan efektif digunakan dalam pembelajaran untuk melatihkan literasi digital siswa.